FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN PERSEPSI TERHADAP KUALITAS LAYANAN PENDAFTARAN PASIEN RAWAT JALAN VIA SMS GATEWAY DI RSUD TUGUREJO SEMARANG - Lina Hanifah; Antono Suryoputro; Septo Pawelas Arso (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2018)
The development of hospital services is followed by the demands of the community to get good quality services, including the use technology. Tugurejo Regional Public Hospital Semarang has implemented an outpatient registration service via SMS gateway since 2015. However, the number of complaints against this service from 2015 to 2017 appeared to be in the list of the highest complaints in the hospital. This study aimed to determine the factors related to the perception of service users. Quantitative research approach with cross-sectional study design was implemented to pursue the objective. Moreover, questionnaires were given to 100 respondents who have used the service at least twice. The research data were processed by univariate and bivariate methods using chi-square statistic test. The results showed that most respondents were young adults (78%), in secondary education level (65%), working (69%), and had low income level (66%). These results showed that the perception of service quality was not good (64%). In addition, the results of the relationship analysis showed that there was a relationship between education level (p= 0,011), motive (p= 0,000), experience (p= 0,044), and expectation (p= 0,000) towards the perception of the quality of the outpatient registration service via SMS gateway. It is suggested for hospitals to provide information to service users if the system is in trouble (error) and provide a means for responsive complaints specifically for outpatient registration services via SMS gateway.